Pengaruh Produk Domestik Bruto, Harga Emas, Dan Suku Bunga Terhadap Return Saham Sektor Perbankan Di Bursa Efek Indonesia - Reynaldo Wiranata; Muhammad Agus Salim; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe goals of this studies are to find out how the probability impacts of stock returns on companies in the banking industry sector on the Indonesia Stock Exchange for the period 2014-2018. In this study, there are several variables used to measure the effect of stock returns, consisting of Gross Domestic Product (GDP), gold prices, and interest rates. The stock return value is taken from the time the gold price closed at the end of the period. Based on the list of companies listed on the Indonesia Stock Exchange, there are many issuers of banking, and from these, 12 banking companies were selected according to the criteria and qualifications of the purposive sampling. The study, using datas analysis techniques, namely by multiple linear regression analysis techniques, using research data, namely panel data. Result of this study provide a statement that the Gross Domestic Product (GDP) has a positive and significant effect on stock returns. In the gold price variable, there is no effect on stock returns. And the interests rates variable give a negative and significant effects on stock returns.Keywords : Issuer Banking, Stock Return, Gross Domestic Product (GDP), Gold Price,  Interest Rate.